Augmented intelligence for industrial chillers - Thant, Hnin Wai (Nanyang Technological University, 2023)
Air conditioning is widely used in industries, manufacturing and commercially. Also part of the heating, ventilation, and air conditioning (HVAC) system, chillers are the primary cooling source used to supply air conditioning to the area. With advancements in augmented intelligence, the capabilities of chiller systems can be improved. Better control and performance monitoring can be achieved through the application of algorithms and machine learning approaches. This will result in increased reliability, lower maintenance costs, and improved energy efficiency. The advantages and uses of augmented intelligence in industrial chillers will be discussed in the following sections, along with how it might influence the way these systems are run and maintained.